2020
DOI: 10.1111/inm.12721
|View full text |Cite
|
Sign up to set email alerts
|

Nurse resilience: A concept analysis

Abstract: Nurse resilience is attracting increasing attention in research and practice. Possession of a high level of resilience is cited as being crucial for nurses to succeed professionally and manage workplace stressors. There is no agreed definition of nurse resilience. A concept analysis was undertaken to examine nurse resilience using a priori selected analysis framework. This concept analysis aims to systematically analyse resilience as it relates to nurses and establish a working definition of nurse resilience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
201
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(222 citation statements)
references
References 170 publications
(174 reference statements)
9
201
1
11
Order By: Relevance
“…In this study, a higher level of emotional loneliness was attributed to lower scores in the personal resilience category, while a higher level of social loneliness was attributed to lower scores in the coping and social support categories, suggesting the importance of building individual resilience and coping behaviours and enhancing social support to combat the negative psychological and mental effects of disease control protocols such as the home quarantine, social distancing, and lockdown measures during the pandemic. Further, this study's result provides support to earlier studies involving the general population and linking personal resilience to reduced anxiety, stress, and depression (Foster et al, 2020;Labrague & De los Santos, 2020) and improved overall mental and psychological health (Cooper et al, 2020). In a study involving young adolescents, adequate coping skills and resilience were identi ed as protective factors against loneliness and other negative effects of social distancing and lockdown measures during the pandemic (Groarke et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, a higher level of emotional loneliness was attributed to lower scores in the personal resilience category, while a higher level of social loneliness was attributed to lower scores in the coping and social support categories, suggesting the importance of building individual resilience and coping behaviours and enhancing social support to combat the negative psychological and mental effects of disease control protocols such as the home quarantine, social distancing, and lockdown measures during the pandemic. Further, this study's result provides support to earlier studies involving the general population and linking personal resilience to reduced anxiety, stress, and depression (Foster et al, 2020;Labrague & De los Santos, 2020) and improved overall mental and psychological health (Cooper et al, 2020). In a study involving young adolescents, adequate coping skills and resilience were identi ed as protective factors against loneliness and other negative effects of social distancing and lockdown measures during the pandemic (Groarke et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Adequate support that originates from peers and family was also observed to be vital to assist an individual in effectively managing stress-provoking situations such as disaster events, emergency crises, and infectious disease outbreaks (Langan et al, 2017). During the COVID-19 pandemic, where stress and loneliness are high, personal resilience, positive coping behaviours, and adequate social support may assist frontline health care workers to adequately cope with the burden associated with the pandemic (Cooper et al, 2020) and sustain their mental health and psychological wellbeing (Labrague et al, 2018;Labrague & De los Santos, 2020). Despite the increasing evidence highlighting the value of building resilience and increasing organisational and social support to assist an individual in attaining positive mental health outcomes (e.g., the reduction of anxiety, stress, depression) during the COVID-19 pandemic, studies looking into how these factors contribute to the curtailment of loneliness among college students during the COVID-19 pandemic remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Personal resilience, or a person's capacity to 'bounce back' or recover quickly from a stressful event (Hart, Brannan, & De Chesnay, 2014), may help nurses cope effectively and endure the burden caused by stressors. In the context of the COVID-19 pandemic, personal resilience may help nurses effectively endure the stress caused by the pandemic (Cooper, Brown, Rees, & Leslie, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Personal resilience, or a person's capacity to ‘bounce back’ or recover quickly from a stressful event (Hart, Brannan, & De Chesnay, 2014), may help nurses cope effectively and endure the burden caused by stressors. In the context of the COVID‐19 pandemic, personal resilience may help nurses effectively endure the stress caused by the pandemic (Cooper, Brown, Rees, & Leslie, 2020). Available studies identified the protective role of personal resilience in nurses during disaster events (Labrague, Hammad, et al, 2018; Turner, 2015) and disease outbreak (Duncan, 2020), suggesting that strengthening nurses’ levels of hardiness and coping abilities can help them manage and deal with stressful situations effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Phili and Karen-Leigh (19) have suggested that nurses in the 21st century have to develop their resilience to deal with occupational problems and maintain their mental health. Resilience and resilient behaviors can potentially help individuals to overcome negative experiences and turn them into positive experiences (20). In the absence of resilience, the working conditions of nurses would become very challenging and cause psychological and biological damages.…”
Section: Introductionmentioning
confidence: 99%